Firm Size dan Debt to Equity Ratio dalam Mempengaruhi Keputusan Menggunakan Instrumen Derivatif untuk Aktivitas Lindung Nilai (Hedging) - Rahmalia, Rani Rodiah; Anita, Widya Febryari; Rahma, Madjidainun (The Double Entry Journal, 2023)
This research is intended to find out how the reasons for firm size and debt to equity ratio can influence the decision to use derivative instruments for hedging activities. The researcher used a purposive sampling technique, namely examining a sample of automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The analytical method used logistic regression analysis using SPSS 26 software. The results showed that firm size had a negative and significant effect on hedging decisions while debt to equity ratio has a positive and significant effect on hedging decisions. The Nagelkerke R Square value is 0.451 and Cox & Snell R Square is 0.338, which indicates that the ability of the independent variable to explain the dependent variable is 0.338 or 33.8% and there are 66.2% other factors outside the model that explain the dependent variable.